Restoration of retinal regenerative potential of Müller glia by disrupting intercellular Prox1 transfer - Eun Jung Lee; Museong Kim; Sooyeon Park; Ji Hyeon Shim; Hyun-Ju Cho; Jung Ah Park; Kihyun Park; Dongeun Lee; Jeong Hwan Kim; Haeun Jeong; Fumio Matsuzaki; Seon-Young Kim; et al. (Nature Communications)
Abstract Individuals with retinal degenerative diseases struggle to restore vision due to the inability to regenerate retinal cells. Unlike cold-blooded vertebrates, mammals lack Müller glia (MG)-mediated retinal regeneration, indicating the limited regenerative capacity of mammalian MG. Here, we identify prospero-related homeobox 1 (Prox1) as a key factor restricting this process. Prox1 accumulates in MG of degenerating human and mouse retinas but not in regenerating zebrafish. In mice, Prox1 in MG originates from neighboring retinal neurons via intercellular transfer. Blocking this transfer enables MG reprogramming into retinal progenitor cells in injured mouse retinas. Moreover, adeno-associated viral delivery of an anti-Prox1 antibody, which sequesters extracellular Prox1, promotes retinal neuron regeneration and delays vision loss in a retinitis pigmentosa model. These findings establish Prox1 as a barrier to MG-mediated regeneration and highlight anti-Prox1 therapy as a promising strategy for restoring retinal regeneration in mammals.